Endophytic actinobacteria of Eleutherine palmifolia as antioxidant producer (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Shabira AP, Tjahjoleksono A, Lestari Y. 2022. Endophytic actinobacteria of Eleutherine palmifolia as antioxidant producer. Biodiversitas 23: 4209-4215. Endophytic actinobacteria can generate bioactive compounds similar to those produced by the host plant. The Eleutherine palmifolia (L.) Merr is an example of a widely utilized host plant in the Dayak community. Flavonoids, which have antioxidant effects, are among the bioactive compounds found in E. palmifolia. The antioxidant activity of bioactive compounds produced by endophytic actinobacteria of E. palmifolia remains unidentified. The aim of this study was to examine the antioxidant activity of bioactive compounds produced by endophytic actinobacteria of E. palmifolia. Antioxidant activity from isolates actinobacteria was determined quantitatively using the DPPH and ABTS methods. Identification of the types of bioactive compound in the samples was identified using TLC assay and bioautography test. Analysis of flavonoid levels was performed using colorimetric aluminum chloride (AlCl3). The result showed that the extraction of six isolates of endophytic actinobacteria with ethyl acetate solvent had different yields. The extract of endophytic actinobacteria EPB 6 isolate produced the highest (0.013%) yield. The extract of endophytic actinobacteria EPB 3 isolate had the best antioxidant activity, with 53.85 mg/mL (DPPH) and 42.43 mg/mL (ABTS). The extract of endophytic actinobacteria EPB 3 isolate and E. palmifolia had the same blue spots in TLC analysis, indicating the presence of bioactive compounds flavonol and flavones groups. The bioautography test of EPB 3 isolate endophytic actinobacteria extract produced yellow color, indicating qualitatively antioxidant activity. The total flavonoid content of the EPB 3 isolate extract was also higher (25.30 QE/mg) than the other five isolates, while it was 46.03 QE/mg in E. palmifolia extract. It is clear from the present study that the endophytic actinobacteria extract can produce antioxidants.
Keywords: Antioxidant, endophytic actinobacteria, Eleutherine palmifolia, flavonoid